2020
DOI: 10.1093/mnras/staa2034
|View full text |Cite
|
Sign up to set email alerts
|

ExoMol line lists – XL. Rovibrational molecular line list for the hydronium ion (H3O+)

Abstract: Abstract A new line list for hydronium (H316O+) is computed. The line list is based on a new ab initio dipole moment surface (CCSD(T)/aug-cc-pVQZ) and a new empirical potential energy surface (PES). The empirical PES of H3O+ was obtained by refining an ab initio surface through a global fit to the experimentally determined ro-vibrational energies collected from the literature covering the ground, $\nu _1^{\pm }$, $\nu _2^{\pm }$, $2\nu _2^{\pm }$, $\nu _3^{\pm }$… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…A line list for the hydronium ion, H 3 O + , has recently been constructed [133] in response to a laboratory study by Bourgalais et al [239] which suggested both that hydronium is likely to be a dominant molecular ion in gaseous exoplanets and that it should be detectable by upcoming space missions.…”
Section: H 3 O + Paper XLmentioning
confidence: 99%
See 1 more Smart Citation
“…A line list for the hydronium ion, H 3 O + , has recently been constructed [133] in response to a laboratory study by Bourgalais et al [239] which suggested both that hydronium is likely to be a dominant molecular ion in gaseous exoplanets and that it should be detectable by upcoming space missions.…”
Section: H 3 O + Paper XLmentioning
confidence: 99%
“…To date the new standard of the States file has being applied to only a number of key/recent line lists namely H 2 O (POKAZATEL) [61] , AlH (AlHambra) [122] , C 2 (8states) [124,194] , HCCH (aCeTY) [130] , CO 2 (UCL-40 0 0) [132] , H 3 O + (eXeL) [133] and TiO (Toto) [126] . A rolling programme is in place for updating the other files so the uncertainty is uniformly available for all sources.…”
Section: Format Of the States And Trans Filesmentioning
confidence: 99%
“…So far only a limited number of ExoMol line lists are available with specified uncertainties in the energy levels. These include important line lists for which MARVEL data were already available, namely those for water [156], AlH [157], 12 C 2 [131], 12 C 2 H 2 [158] and 48 Ti 16 O [158], and recently produced line lists including those for CO 2 [159], H 3 O + [160] and NH 3 [161]. The present study is the first in a series where a MARVEL analysis is performed with the intention of updating an available line list.…”
Section: Discussionmentioning
confidence: 99%
“…Line list calculations employed the variational nuclear motion program TROVE (Yurchenko, Thiel & Jensen 2007), which was extended to treat linear triatomic molecules in this work. Benchmarking was performed against the triatomic nuclear motion code DVR3D (Tennyson et al 2004) to ensure the validity of the TROVE implementation.…”
Section: Methodsmentioning
confidence: 99%